2013
DOI: 10.1039/c3ta12737k
|View full text |Cite
|
Sign up to set email alerts
|

An investigation about the use of mixtures of sulfonium-based ionic liquids and propylene carbonate as electrolytes for supercapacitors

Abstract: This study describes the use of mixtures of the ionic liquid (IL) trimethyl-sulfonium bis [(trifluoromethyl) sulfonyl]imide (Me 3 STFSI) and propylene carbonate (PC) as electrolytes for carbon-based electrochemical double layer capacitors (EDLCs). Two different mixtures have been investigated. The first one contained the maximum amount of Me 3 STFSI (3.8 mol L À1 ) soluble in PC at room temperature (RT). The second one contained 1.9 mol L À1 of Me 3 STFSI, which is the concentration featuring the highest co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…476 Vali et al 151 reported that the type of conducting salt could greatly affect the electrochemical stability of Al current collectors in an organic solvent. Brandt et al 314 reported that the possible anodic oxidation of Al current collectors could strongly affect the operation cell voltage of EDLCs when IL-organic electrolyte mixtures (i.e., [Me 3 S][TFSI]-PC) were used. This condition could lead, in turn, to a much lower electrochemical stability when compared to both NaPF 6 -and NaClO 4 -based electrolytes.…”
Section: Compatibility With Current Collectorsmentioning
confidence: 99%
“…476 Vali et al 151 reported that the type of conducting salt could greatly affect the electrochemical stability of Al current collectors in an organic solvent. Brandt et al 314 reported that the possible anodic oxidation of Al current collectors could strongly affect the operation cell voltage of EDLCs when IL-organic electrolyte mixtures (i.e., [Me 3 S][TFSI]-PC) were used. This condition could lead, in turn, to a much lower electrochemical stability when compared to both NaPF 6 -and NaClO 4 -based electrolytes.…”
Section: Compatibility With Current Collectorsmentioning
confidence: 99%
“…1b). This optimal ratio (50:50% w.t) has been widely employed as mixture electrolyte for electrochemical energy storage devices in presence of different ionic liquid chemical structures, as for example Me 3 NHTFSI:PC, PYRNO 3 :PC, Me 3 STFSI:PC or PYR 14 TFSI:PC in the field of supercapacitors [29,24,23]. This ratio demonstrated in all the aforementioned cases physical-chemical properties (h and s) close to pure PC containing salt electrolytes (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…PYR 14 TFSI or Me 3 STFSI) and organic solvents (e.g. PC) showed h and s values close to pure PC containing 1 M Et 4 NBF4, which exhibited the highest conductivity and lowest viscosity values by comparison between both the pure ionic liquids and the corresponding mixtures [23,24]. Based on this criteria, this mixture ratio was chosen as an optimal electrolyte for the electrochemical performances reported in this study.…”
Section: Electrochemical Performance Of Single Electrodes (Sinws) Andmentioning
confidence: 92%
“…[21] In the last years several research efforts have concentrated on the application of mixtures of pyrrolidinium-based ILs and organic carbonates as EDLC electrolytes. [22][23][24][25][26] Using these mixtures, an operative voltage higher than 3.0 V could be retained while decreased viscosities and increased conductivities with respect to neat ILs could be reported. [22,23].…”
Section: Introductionmentioning
confidence: 93%